2013
DOI: 10.1111/ijfs.12155
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenic potential of fresh and frozen cassava on retail sale in three Irish cities: a snapshot survey

Abstract: Summary Imported cassava roots can be found on retail sale in several Irish cities and towns. Fresh roots (n = 36 roots) and peeled frozen root pieces (n = 28 packs) were randomly purchased from five retailers in Belfast, Dublin and Limerick and assayed for cyanogenic potential (CNp). Total CNp of fresh root parenchyma varied from 37.5 to 242.9 mg kg−1 as HCN, dry weight basis – dwb), averaging 104.4 mg kg−1 HCN (dwb). Total CNp of frozen root parenchyma (n = 28 packs) ranged from 28.5 to 258.6 mg kg−1 HCN (dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Overall, the mean total CNp of purchased fresh roots assayed in the present study (59.0 mg kg −1 as HCN fwb) exceeded that of a sample of 36 imported Costa Rican roots (34.5 mg kg −1 fwb) purchased in Ireland (O’Brien et al ., 2013), but was lower than that of a sample of 25 Costa Rican roots (73 mg kg −1 fwb) purchased in Denmark (Kolind‐Hansen & Brimer, 2010). The results indicated that an individual Singaporean root from the present study had a CNp of 120.5 mg kg −1 (fwb) and 387.7 mg kg −1 (dwb), which exceeded the high‐CNp ‘outliers’ of 242.9 mg kg −1 (dwb) in the Irish study (O’Brien et al ., 2013) and 351 mg kg −1 (dwb) in the Danish study (Kolind‐Hansen & Brimer, 2010). The high degree of variability in CNp noted in each of the three country‐of‐origin sub‐samples is hardly surprising: it has long been known that variations in root parenchymal CNp occur not only in roots of different cultivars, but amongst roots of the same cultivar, and even amongst roots of the same plant (Bokanga, 1994).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Overall, the mean total CNp of purchased fresh roots assayed in the present study (59.0 mg kg −1 as HCN fwb) exceeded that of a sample of 36 imported Costa Rican roots (34.5 mg kg −1 fwb) purchased in Ireland (O’Brien et al ., 2013), but was lower than that of a sample of 25 Costa Rican roots (73 mg kg −1 fwb) purchased in Denmark (Kolind‐Hansen & Brimer, 2010). The results indicated that an individual Singaporean root from the present study had a CNp of 120.5 mg kg −1 (fwb) and 387.7 mg kg −1 (dwb), which exceeded the high‐CNp ‘outliers’ of 242.9 mg kg −1 (dwb) in the Irish study (O’Brien et al ., 2013) and 351 mg kg −1 (dwb) in the Danish study (Kolind‐Hansen & Brimer, 2010). The high degree of variability in CNp noted in each of the three country‐of‐origin sub‐samples is hardly surprising: it has long been known that variations in root parenchymal CNp occur not only in roots of different cultivars, but amongst roots of the same cultivar, and even amongst roots of the same plant (Bokanga, 1994).…”
Section: Resultsmentioning
confidence: 71%
“…Phosphate buffers (pH 4.0, 6.0 and 7.0), colourimetric reagents, buffered linamarase preparation, linamarin standard solution (for testing linamarase ) and KCN standard solution were prepared as described by O’Brien et al . (2013).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, there appears to be a clear cause for concern arising from the small random sample of Indonesian roots tested in Singapore by O'Brien et al: not only did the mean overall CNp of 59•5 mg/kg HCN (fwb) exceed the aforementioned CAC maximum level, but more than half of the individual roots sampled (fifteen of twenty-four) exceeded it, with one root having a CNp of 99•5 mg/kg HCN (fwb) (27) . Similarly, while a random sample of ten packs of frozen parenchyma from the Philippines tested in Ireland was fully compliant with the CAC requirement for sweet cassava (52) , the reported CNp of 52 mg/kg HCN (fwb) in frozen Vietnamese parenchyma on retail sale in Australia tested by Burns et al (30) exceeds the CAC maximum level and might possibly indicate a problem.…”
Section: Discussionmentioning
confidence: 93%
“…║Data from three samples of frozen root parenchyma on retail sale in Australia, reported by Burns et al (30) . ¶Previously unpublished data from ten packs of frozen root parenchyma, on retail sale in Ireland, from O'Brien et al study (52) . **Data from four samples of cassava flour, reported by Egan et al (53) .…”
Section: Discussionmentioning
confidence: 99%